Examination of health literacy and personal impact of epilepsy in patients with epilepsy - Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Yildiz, Esra (Academic Press Inc Elsevier Science, 2023)
Aim: We conducted this study to examine the impact of health literacy on the personal impact of epilepsy in patients with epilepsy.Method: We conducted this cross-sectional and correlational study with 125 individuals who were admitted to the neurology outpatient clinic of a university hospital in eastern Turkey, who met the research criteria, and who accepted to participate in the study. We collected the data by using the Descriptive Information Form (DIF), The Personal Impact of Epilepsy Scale (PIES), and Health Literacy Scale (HLS).Results: We found that the mean HLS total score of the participants was 104.84 +/- 22.88. We also found the mean PIES total score to be 27.08 +/- 18.56. Regression results using PIES as a dependent variable reported that the model created was statistically significant (F (21,83) = 11.398, p < 0.05). Among the variables included in the model, income status and HLS were negative (beta =-0.209; beta =-0.194; beta =-0.364, respectively) predictors of the PIES total score. However, seizure status in the last year, number of drugs used, and seizure type were positive predictors of the PIES total score. We found that the variables included in the analysis explained 74% of the total PIES score.Conclusion: In conclusion, the health literacy level (HLL) of the participants was sufficient or very good, and the effect of the disease on individuals with epilepsy was low. The effect of the disease on individuals with epilepsy decreased as the level of health literacy increased.(c) 2023 Elsevier Inc. All rights reserved.
Keywords: Epilepsy; Personal effect; Health literacy; Patient